Modulation of fatty acid metabolism and tricarboxylic acid cycle to enhance the lipstatin production through medium engineering in Streptomyces toxytricini. (August 2016) - Kumar, Punit; Dubey, Kashyap Kumar
Highlights: Non-conventional carbon source soya flour and sesame oil were used to increase the lipstatin yield. Tricarboxylic acid cycle was modulated through intermediates balancing. Role of amino-acids, vitamins and cofactors in lipstatin biosynthesis was investigated. Abstract: This work investigated the potential of medium engineering to obtain maximum biomass, non-conventional carbon sources for lipstatin production and modulation of tricarboxylic acid (TCA) cycle to promote lipstatin synthesis. It was found that 2:3 carbon and nitrogen ratio, produced maximum biomass of 7.9 g/L in growth medium and 6.6 g/L in pre-seed medium. Among the studied non-conventional carbon sources i.e., soya flour 40 g/L and sesame oil 30 mL/L were found producing 1109.37 mg/L (1.24-fold of control) and 1196.75 mg/L (1.34-fold of control) lipstatin respectively. Supplementation of TCA cycle intermediates revealed that NADH and succinic acid showed lipstatin production to 1132.99 mg/L and 1171.10 mg/L respectively. Experimental outcome was validated in 7 L bioreactor and produced 2242.63 mg/L lipstatin which was ∼14% higher than shake flask.